Cranially Directed Upper Instrumented Vertebrae Screw Angles Are Associated With Proximal Junctional Kyphosis in Adult Spinal Deformity Surgery. Issue 10 (15th May 2023) - Chen, Jeffrey W.; Longo, Michael; Chanbour, Hani; LaBarge, Matthew E.; Abtahi, Amir M.; Stephens, Byron F.; Zuckerman, Scott L.
Abstract : Study Design: A retrospective cohort study. Objective: To evaluate the impact of the upper instrumented vertebral (UIV) screw angle in adult spinal deformity (ASD) surgery on: (1) proximal junctional kyphosis/failure (PJK/F), (2) mechanical complications and radiographic measurements, and (3) patient-reported outcome measures (PROMs). Summary of Background Data: The effect of UIV screw angle in ASD surgery on patient outcomes remains understudied. Materials and Methods: A single-institution, retrospective study was undertaken from 2011 to 2017. UIV screw angle was trichotomized into positive: cranially directed screws relative to the superior endplate (2°≤θ), neutral: parallel to the superior endplate (−2°<θ<2°), and negative: caudally directed screws relative to the superior endplate (−2°≥θ). The primary outcome was PJK/F. Secondary outcomes included remaining mechanical complications, reoperation, and PROMs: Oswestry Disability Index, Numeric Rating Scale (NRS) back/leg, and EuroQol. Regression controlled for age, body mass index, postoperative sagittal vertical axis (SVA), and pelvic incidence lumbar-lordosis mismatch. Results: Among 145 patients undergoing ASD surgery, UIV screw angles were 35 (24.1%) cranially directed, 24 (16.6%) neutral, and 86 (59.3%) caudally directed. PJK occurred in 47(32.4%) patients. Positive screws were independently associated with increased PJK [odds ratio (OR)=4.88; 95% CI, 1.85–13.5, P =0.002] and PJF (OR=3.06; 95% CI, 1.32–12.30, P =0.015). Among 108 (74.5%) patients with lower thoracic UIV, PJK occurred in 38 (35.1%). Cranially directed screws were independently associated with an increased odds of PJK (OR=5.56; 95% CI, 1.86–17.90, P =0.003) with a threshold of 0.2° (area under the curve =0.65; 95% CI, 0.54–0.76, P <0.001), above which the risk of PJK significantly increased. No association was found between positive screw angle and PJF (OR=3.13; 95% CI, 0.91–11.40, P =0.073). Because of the low number of patients with an upper thoracic UIV (N=37, 25.5%), no meaningful conclusions could be drawn from this subgroup. There was no association between UIV screw angle and remaining mechanical complications, reoperations, postoperative SVA and T1-pelvic angle, or PROMs. Conclusions: Cranially directed UIV screw angles increased the odds of PJK in patients with lower thoracic UIV. Meticulous attention should be paid to the lower thoracic UIV screw angle to mitigate the risk of PJK in ASD.